VD_FINDINFO HC / 2025 / 189 vom 5. Februar 2025 - VD Tribunal cantonal (2025)
MESURE PRÉPROVISIONNELLE, PLACEMENT D'ENFANTS, DÉCISION D'IRRECEVABILITÉ | 310 CC, 265 CPC (CH), 308 al. 1 let. b CPC (CH)